2011
DOI: 10.1037/a0023915
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be…included in an event file: Integration and retrieval of distractors in stimulus–response episodes is influenced by perceptual grouping.

Abstract: The binding of stimulus and response features into stimulus-response (S-R) episodes or "event files" is a basic process for the efficient control of behavior. However, relevant information is usually accompanied by information that is irrelevant for the selection of action. Recent studies showed that even irrelevant information is bound into event files. In this study, we investigated the boundary conditions of distractor-response binding and subsequent distractor-based response retrieval processes. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
119
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 49 publications
9
119
4
Order By: Relevance
“…It seems that a retrieval of event files can be mediated by perceptual features (e.g., Frings & Rothermund, 2011;Hommel, 2004;Mayr & Buchner, 2006), by word entries in a lexicon (Giesen & Rothermund, 2011;Rothermund et al, 2005), by location information (Frings & Moeller, 2010), and also by conceptual representations of irrelevant stimuli-as evidenced by the results of the present study.…”
Section: Discussionsupporting
confidence: 51%
“…It seems that a retrieval of event files can be mediated by perceptual features (e.g., Frings & Rothermund, 2011;Hommel, 2004;Mayr & Buchner, 2006), by word entries in a lexicon (Giesen & Rothermund, 2011;Rothermund et al, 2005), by location information (Frings & Moeller, 2010), and also by conceptual representations of irrelevant stimuli-as evidenced by the results of the present study.…”
Section: Discussionsupporting
confidence: 51%
“…In accordance with this statement, Frings andvan Dam andHommel (2010) showed that the binding between features of two objects is dependent on the spatial location of these objects. The integration between elements pertaining to different objects only binds with greater intensity if they share a spatial location (Frings & Rothermund, 2011;van Dam & Hommel, 2010). Moreover, concerning the interaction between location and especially motor response, Henderson (1996) explained this as a result of their strong intradomain coupling.…”
Section: Discussionmentioning
confidence: 53%
“…Kahneman and colleagues, in their original definition of the object file, proposed that the different bindings that we make are classified and addressed via location codes; that is, the feature content of a file is only available if a probe object can be spatially related to a prime object (Kahneman et al, 1992). In accordance with this statement, Frings andvan Dam andHommel (2010) showed that the binding between features of two objects is dependent on the spatial location of these objects. The integration between elements pertaining to different objects only binds with greater intensity if they share a spatial location (Frings & Rothermund, 2011;van Dam & Hommel, 2010).…”
Section: Discussionmentioning
confidence: 57%
“…However, these experiments only assessed S-R effects across immediate or short lags between encoding and retrieval. The exception to this is Experiment 2b of Frings and Rothermund (2011), which presented a yellow circle between presentations of letters (the letters being the stimuli of experimental interest). Thus, despite the presence of an intervening stimulus, it was 570 THE QUARTERLY JOURNAL OF EXPERIMENTAL PSYCHOLOGY, 2016, 69 (3) consistent across trials and had little perceptual similarity to the main experimental stimuli.…”
Section: Discussionmentioning
confidence: 99%